Klasifikasi Data UMKM Di Desa Wilayut Untuk Mengetahui Dan Upaya Peningkatan Ekonomi Masyarakat - Diah Tri Novitaningrum; Abdul Hafidz Rosydi Fuady; Dwi Yuliana Pertiwi; Rahayu Mardikaningsih; Didit Darmawan; Siti Nur Halizah; Eli Retnowati; Rommy Hardyansah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The results of data classification and field surveys by Unsuri students in Wilayut Village, Sukodono District. Has potential MSMEs in the form of businesses that produce a product of goods or services. However, in marketing activities, business actors are still doing conventionally and the use of branding strategies is also not optimal. So that the scope of marketing is still limited, making the business being run unable to develop properly. KKN activities as a form of community service in Wilayut Village aim to provide social contributions from the campus to the community as well as for the community to get help with thoughts and energy to carry out village development and solve community problems in the village. The method used is the MSME data classification method and partner participation by providing direction on the benefits of social media. Participating in contributing to the classification of MSME data in Wilayut Village and helping business actors in increasing the existence of cilok kuah seblak bu tin as one of the MSMEs engaged in the food sector.